Sin taxes in differentiated product oligopoly: An application to the butter and margarine market - Rachel Griffith; Lars Nesheim; Martin O'Connell (Centre for Microdata Methods and Practice (cemmap), 2010)
There is policy interest in using tax to change food purchasing behaviour. The literature has not accounted for the oligopolistic structure of the industry. In oligopoly the impact of taxes depend on preferences, and how firms pass tax onto prices. We consider a tax on saturated fat. Using transaction level data we find that the form of tax and firms' strategic behaviour are important determinants of the impact. Our results suggest that an excise tax is more efficient than an ad valorem tax at reducing saturated fat purchases and an ad valorem tax is more efficient at raising revenue.
Keywords: L13; H20; I18; 330; Steuerpolitik; Konsumentenverhalten; Offenbarte Präferenzen; Oligopol; Streichfett